Health-related quality of life of metastatic prostate cancer patients treated with prostate Radiotherapy - Heba Maged Ayoub; Maha Lotfy Zamzam; Eman Essam Elsemary; Ihab Mohamed Hassanin; Fifi Mostafa Elsayed (BMC Cancer, 2023)
Abstract Background The impact of prostate radiotherapy on patient-reported health-related quality of life (HRQoL) significantly influences the outcomes of metastatic prostate cancer. We measured and compared HRQoL of metastatic prostate cancer patients who received cytoreductive prostate radiotherapy. Methods Between November 23, 2020, and November 21, 2022, we recruited 70 metastatic prostate cancer patients at the Department of Clinical Oncology at Suez Canal University Hospital. Patients were eligible if they had synchronous and metachronous histopathological confirmed metastatic adenocarcinoma and an Eastern Cooperative Oncology Group performance status ≤ 2. Random allocation was performed for either definitive local radiotherapy concurrent with the standard androgen deprivation therapy (ADT) or to the standard ADT alone. Definitive radiotherapy was delivered conventionally (70 Gy/35 fractions) or through the hypofractionated regimen (55 Gy/20 fractions). Patients completed the comprehensive European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-PR25) at baseline, then at three-month intervals for one year. The primary endpoint was patient-reported HRQoL, with secondary endpoints including toxicity and radiographic progression-free survival (rPFS). Mean HRQoL scores between groups were compared using the independent samples t-test. Results We observed clinically significant improvements in urinary and bowel functions between baseline, 3-month, 6-month, and 12-month intervals after receiving definitive prostate radiotherapy. Patients in the radiotherapy group had significantly lower urinary symptoms scores than the control group. However, sexual activity and functioning showed significant deterioration. Conclusion Cytoreductive prostate radiotherapy in metastatic prostate cancer patients significantly improved urinary functioning, preserved bowel functioning but was associated with worsening of sexual functioning. Trial Registration This trial was registered on (27/04/2023) with pactr.samrc.ac.za, PACTR202305854600529, URL: https://pactr.samrc.ac.za/TrialDisplay.aspx?TrialID=25510 .